Studi Pembiasaan Shalat Dhuha dalam Membina Akhlak Siswa di Madrasah Ibtidaiyah Al-Khoeriyah 1 Kabupaten Garut - Ajid Abdul Majid (JIECO: Journal of Islamic Education Counseling, 2021)
Based on the results of the previous research conducted by the researchers at several Madrasah Ibtidaiyah in Garut, there are still many students who unwilling to do the dhuha prayer even though there are so much benefits. This is because the planning, implementation, and evaluation have not been optimal. So, it has negative impact to the morals of the students. The purpose of this study is to obtain an overview of how the planning, implementation, evaluation of problems and solutions of habituation of dhuha prayer for building student’s morals at Madrasah Ibtidaiyah in Garut. This research used a qualitative approach with case study method and data collection techniques are carried out through observation, interviews and documentation studies. While the data sources are principals, teachers and students. The purpose of this study is to find out how to plan, implement, evaluation, obstacles and solutions to build the students habitual of dhuha prayer in Madrasah Ibtidaiyah Al-Khoeriyah Garut. The results of this study are: a) In the planning aspects, habituation starts from determining the purpose of the study, determining materials, programs, activities and evaluation tools that will be used, b) In the implementation aspects, habituation of dhuha prayer is individually in the mosque with guidance from the teacher, the teacher is giving the example, explaining moral excellence, benefits and procedurs about dhuha prayer. Students who are included in the habituation dhuha prayer program are only sixth grade, c) In the evaluation aspects, habituation is carried out every middle semester and final semster. The evaluation included of planning, implementation and the results of habituation, d) The problems of habituation dhuha prayer are limited facilities and teachers who guide, e) The solution to this problem, by collaborating with the mosque prosperity council in the surrounding neighborhood.